FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI GURU DI ERA TRANSFORMASI DIGITAL - Ulfa, Marya; Firmansyah, Diyan; Junaidah, Junaidah; Hadiati, Eti (STKIP Pesisir Selatan, 2026)
This study aims to analyze various factors influencing teacher work motivation amidst the digital transformation in education. The research method used is descriptive qualitative with a library research approach, which aims to provide a systematic overview of the phenomenon of teacher work motivation. The primary data sources consist of journal articles selected based on their relevance to the research topic. Data collection was carried out through documentation techniques and systematic literature searches through journal databases such as Google Scholar, ScienceDirect, and other sources covering the years 2020-2025, as well as books relevant to the topic. Meanwhile, data analysis used content analysis to synthesize the findings from the literature sources. The results show that teacher work motivation is influenced by internal factors such as digital literacy, intrinsic motivation, and TPACK competencies, as well as external factors including organizational support, principal leadership, teacher welfare, the work environment, and opportunities for professional development. The main challenges that arise include technostress and the gap in technology access. In conclusion, strengthening teacher work motivation in the digital era requires a synergy between individual capacity building and systemic support from educational institutions.